Arthroscopic Shoulder Labral Repair Using Knotless All-Suture Anchor With Suture Tape - Jayson Lian, M.D.; Michael B. Banffy, M.D. (Arthroscopy Techniques)
Advances in shoulder arthroscopy have in large part been due to innovation in suture anchor technology. In recent years, shoulder instability surgery has been revolutionized by knotless all-suture anchor devices. All-suture anchors can prevent complications such as a free-floating intra-articular hard-body anchor while still preserving pullout strength using a smaller bone tunnel. Knotless technology can additionally reduce surgical variability by eliminating knot tying and knot stacks. Surgeons and engineers are finding ways to make smaller, stronger, and less traumatic anchors for repair of soft tissues. In this article, we describe an arthroscopic shoulder labral repair technique using a knotless all-suture anchor with suture tape.